ESG and Financial Performance in the Healthcare Industry: A Theory-Based Systematic Literature Review - Rahmayanti Cahyaningtyas; Agus Widarsono; Aristanti Widyaningsih; Rozmita Dewi Yuniarti Rozali (JURNAL ECONOMINA, 2026)
This study aims to examine the theoretical mechanisms underlying the relationship between Environmental, Social, and Governance (ESG) and financial performance in the healthcare industry and to identify the dominant financial proxies and sustainability pillars discussed in the literature. The study employs a Systematic Literature Review (SLR) method following the PRISMA guidelines and combines content analysis with thematic analysis. The literature search was conducted in the Scopus database using keywords related to ESG, financial performance, and the healthcare sector. From an initial dataset of 60,929 records, 17 articles met the inclusion criteria for further analysis. The findings reveal that the ESG-financial performance relationship in the healthcare industry can be explained through five major thematic clusters: capital cost efficiency through transparency signaling, institutional compliance and social legitimacy, value dynamics in stakeholder management, ESG transformation into intangible assets, and cost trade-offs with supply chain coordination. The review also indicates that the financial impact of ESG is heterogeneous and influenced by industry context, market competition, and the characteristics of each ESG pillar. ESG practices may enhance investor confidence, legitimacy, and competitive advantage, but they may also impose initial costs that reduce short-term profitability.